A premontreiek és az Oltáriszentség tisztelete - Sári Zsolt (2003)
The author in his essay introduces the relationship of the Eucharist and the Premonstrant Order. The order was founded by St. Norbert in 1120 in Coucy wood in France. The order has five intentions: chorus prayers, the veneration of the Eucharist and Virgin Mary, to pastorate, self denial and penance. In Hungary the order settled in the lifetime of St. Norbert in 1130 when II. Stephen invited monks from Premontre. They built the monastery in Váradhegyfok (near to Nagyvárad) for the veneration of the first martyr, St. Stephen. One of the basic feature of the order's spirituality is the adoration of Christ's divinity and humanity in the Eucharist. The author differentiates four levels in the veneration of the Eucharist: 1. the holy mass the culmination of all liturgies, 2. Holy Thursday, feast of the birth of the Eucharist, 3. Corpus Christi, the feast of the Eucharist, 4. the different liturgical and paraliturgical worships like, adoration of the Eucharist, litany of the Eucharist, Corpus Christi confraternities, altar associations etc.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Filozófia, etika és vallástudományok